CONSUMER PREFERENCE ANALYSIS AND DEMAND FOR MEAT IN KANO METROPOLIS: A HEDONIC MODEL APPROACH (FUDMA JOURNAL OF SCIENCES, 2023)
This study examined consumer preference and demand analysis for meat in Kano metropolis. Primary data were collected through a well-structured questionnaire, a total of one hundred and fifty 158 member of household was selected for this study. It was revealed that majority (72.2%) of consumers earns monthly income of N15, 000-N55, 000. Hedonic regression for meat attributes affecting Price shows that meat flavour (Good) was the reference group while meat with bad flavour was entered as dummy variables and the result shows that meat with good flavour was statistically significant at (P< 0.05) with positive coefficient implying that for any unit increase in these variables, buyers would be willing to pay premium because they showed higher significant buyer preference level, results also shows that meat with good taste was statistically significant at (P< 0.05) with positive coefficient this implying that meat with good taste are point of interest for the consumers and they are ready to pay high premium to buy the commodities with this attributes. It was revealed that amount of fat (high ) was found to be statistically significant  with a negative coefficient, implying that meat with low fat is more preferable and are selling at higher prices in the study area.  Low income of consumer was the highest constraints associated with meat consumption in the study area, with a mean rank of 3.01, followed by high selling price with the mean rank of 3.63 and food safety with 4.20.
Keywords: Consumer Preference; Analysis; Demand; Meat; Kano